The Relationship between Mothers’ Level of Knowledge and Attitudes and the Provision of BCG Immunization - Syinthia Rahmi, Fani; Dahlan, Febry Mutiariami; Wirenviona, Rima; Ramadhaniati, Fitri; Yuli Afni Amran, Vitri (Rajaki of Tulip Medika Publisher, 2026)
The immune system of infants is still developing, making them more susceptible to infectious diseases, including tuberculosis (TB). One of the effective preventive measures against TB is Bacillus Calmette–Guérin (BCG) immunization. However, BCG immunization coverage in the regency has only reached 93.13%, with Pakandangan Health Center ranking as the second lowest, achieving only 64% coverage out of a target population of 242 infants. This study aimed to examine the relationship between mothers’ level of knowledge and attitudes and the provision of BCG immunization in Korong Pakandangan, Enam Lingkung District, in 2025. An analytic survey with a cross-sectional design was conducted among 92 mothers who had infants aged 0–11 months, using total sampling. Data were analyzed using univariate and bivariate analyses. The results showed that 60.9% of respondents had low knowledge regarding BCG immunization, 56.5% had negative attitudes toward BCG immunization, and 66.3% had provided BCG immunization to their infants. Bivariate analysis revealed a significant relationship between mothers’ knowledge and BCG immunization provision (p = 0.001) as well as between mothers’ attitudes and BCG immunization provision (p = 0.008). In conclusion, mothers’ knowledge and attitudes are significantly associated with the provision of BCG immunization. It is recommended that health workers, particularly community health volunteers (posyandu staff), enhance the frequency of health education to improve awareness of the importance of BCG immunization for infants.